What drives successful startups? - an analysis of founder backgrounds of high potential startups - Wolff, Jonas Benedikt (2022)
This study examines the influence of founder backgrounds on the success of a start up. The analyzed factors are education, gender, previous work experience and theoretical knowledge. Three success scenarios are analyzed using a logistic regression model. The findings demonstrate that, depending on the success scenario, different aspects will have a significant impact on the odds of success. It is found that education, previous industry experience and previous founding experience have a significant positive impact on the odds of success in two of the three scenarios. However, no significance could be discovered for the attendance of an Ivy League university.